Consideration of different scoring approaches for a verbal incidental learning measure from the WAIS-IV using hippocampal volumes. Issue 1 (2nd January 2023) - Hammers, Dustin B.; Miranda, Michelle; Abildskov, Tracy J.; Tate, David F.; Wilde, Elisabeth A.; Spencer, Robert J.
Abstract: Objective: While Spencer's verbal incidental learning (IL) task—from Vocabulary and Similarities subtests of the WAIS—has been validated relative to traditional memory measures and Alzheimer's disease (AD) pathology, the effectiveness of the particular scoring method used has not been assessed relative to alternative scoring weightings. The purpose of this study was to compare original and alternative scoring methods of this IL task by using an AD biomarker-benchmark to arrive at an optimal approach. Methods: Fifty-five memory-clinic patients aged 59–87 received neuropsychological assessment, measures of IL, and quantitative brain imaging. Partial correlation coefficients with total hippocampal volume—controlling for age, sex, and intracranial volume—were assessed across several IL scoring methods, and partial correlations with measures of memory were examined to evaluate convergent validity. Results: IL scoring methods maximizing the contribution of paired-associate-recall-performance were significantly correlated with both hippocampal volumes and traditional memory measures, whereas discrimination-emphasized scoring methods were not. Conclusions: IL scoring methods emphasizing memory paired-associate recall appeared to be preferable to those emphasizing memory discrimination. Administration of the IL- Similarities subtest alone, without IL- Vocabulary, may strike a balance between strength of relationships with both hippocampal volumes and standard memory measures, while also limiting administration time.